2018
DOI: 10.1038/s41598-018-31191-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Khat (Catha edulis) use on catalytic activities of major drug-metabolizing cytochrome P450 enzymes and implication of pharmacogenetic variations

Abstract: In a one-way cross-over study, we investigated the effect of Khat, a natural amphetamine-like psychostimulant plant, on catalytic activities of five major drug-metabolizing cytochrome P450 (CYP) enzymes. After a one-week Khat abstinence, 63 Ethiopian male volunteers were phenotyped using cocktail probe drugs (caffeine, losartan, dextromethorphan, omeprazole). Phenotyping was repeated after a one-week daily use of 400 g fresh Khat leaves. Genotyping for CYP1A2, CYP2C9, CYP2C19, CYP2D6, CYP3A5 were done. Urinary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 56 publications
0
17
0
Order By: Relevance
“…Phenoconversion is most likely to influence PGx results in African populations due to complex health interventions that include herbal medicines, although some enzymes such as CYP2D6 are not easily induced. Khat ( Catha edulis Forsk ), a psychoactive herb commonly used in East Africa, has been identified as a potent inhibitor of the CYP2D6 enzyme (which metabolises up to 25% of prescribed medications) [ 66 ]. Therefore, environmental factors such as regional lifestyles and co-medication should be considered in future studies and in the interpretation of clinical pharmacogenetically guided drug prescription.…”
Section: Challenges In Genotyping Pharmacogene Variantsmentioning
confidence: 99%
“…Phenoconversion is most likely to influence PGx results in African populations due to complex health interventions that include herbal medicines, although some enzymes such as CYP2D6 are not easily induced. Khat ( Catha edulis Forsk ), a psychoactive herb commonly used in East Africa, has been identified as a potent inhibitor of the CYP2D6 enzyme (which metabolises up to 25% of prescribed medications) [ 66 ]. Therefore, environmental factors such as regional lifestyles and co-medication should be considered in future studies and in the interpretation of clinical pharmacogenetically guided drug prescription.…”
Section: Challenges In Genotyping Pharmacogene Variantsmentioning
confidence: 99%
“…They result in the feeling of well-being and mental alertness as well as excitement in users, but they have a number of untoward effects as well, which is why their use is banned in many countries. As aforementioned, the previous research shows neither cathine nor cathinone appears to be responsible for the inhibition of cytochrome subenzymes [9,10,12,28]. Therefore, investigating the molecular mechanism of cytochrome subenzymes' inhibition by khat is still very much needed.…”
Section: Pharmacokinetic Studymentioning
confidence: 99%
“…Previously, a number of studies have been carried out to establish the effects of khat on the cytochrome P450 (CYP450) enzyme family [9][10][11]. In one of these studies, the effects of the khat extract on the activity of three in vitro human recombinant cytochrome P450 (CYP)2C9, CYP2D6, and CYP3A4 enzymes were checked and compared with that of cathinone, a constituent of khat [12].…”
Section: Introductionmentioning
confidence: 99%
“…57 A study in healthy users of khat showed that the use of this plant resulted in a CYP2D6 inhibition and a marginal effect on CYP3A4 and CYP2C19 activities, owing to competitive inhibition by cathinone. 58 Potential interactions between cathinones and DAA are limited.…”
Section: Cathinonesmentioning
confidence: 99%